Vertebrae localization in pathological spine CT via dense classification from sparse annotations. - Glocker, Ben; Zikic, D.; Konukoglu, Ender; R. Haynor, David; Criminisi, Antonio (2013 Medical Image Computing and Computer-Assisted Intervention, 2013)
Accurate localization and identification of vertebrae in spinal imaging is crucial for the clinical tasks of diagnosis, surgical planning, and post-operative assessment. The main difficulties for automatic methods arise from the frequent presence of abnormal spine curvature, small field of view, and image artifacts caused by surgical implants. Many previous methods rely on parametric models of appearance and shape whose performance can substantially degrade for pathological cases.